Blue Whale Body Condition Assessed Over a 14-Year Period in the NE Pacific: Annual Variation and Connection to Measures of Ocean Productivity - Wachtendonk, Rachel; Calambokidis, John; Flynn, Kiirsten (Frontiers in Marine Science, 2022)
Large marine mammals can serve as an indicator of the overall state of the environment due to their apex position in marine food webs and their functions as sentinels of change. Reductions in prey, driven by changes in environmental conditions can manifest in reduced fat stores that are visible on whales. We developed a non-invasive technique using photographs of blue whales taken on the US west coast from 2005-2018 (n=3,660) and scored body condition based on visible undulations from the vertebral processes and body shape. We analyzed patterns in the body condition of whales across years and their relation to oceanographic conditions. Females with calves had significantly poorer body conditions and calves had significantly better body conditions compared to other adult whales (Chi-Square, x2 = 170.36, df=6, p<2.2e-16). Year was a significant factor in body condition (Chi-Square, x2 = 417.73, df=39, p<0.001). The highest proportion of whales in poor body condition was observed for 2015 (one of the only two years along with 2017 where >50% had poor body condition) coincides with the marine heat wave that affected the NE Pacific 2014-2016. A cumulative mixed model examining the relationship between body condition and environmental variables revealed that negative Pacific Decadal Oscillation and longer upwelling seasons correlated with better blue whale body condition, likely to be due to higher primary productivity and prey availability. This study indicates that with an adequate scoring method, photographs collected during boat based surveys can be used to effectively evaluate whale health in response to a changing ocean.